Landfills as a potential source and origin of microplastics: Formation, composition, and environmental risks - Gupta, Anshu; Verma, Akanksha; Atri, Rakesh Kumar (Frontiers in Environmental Science, 2025)
Globally, plastic waste generation has reached approximately 300 million tons annually, accounting for more than 10% of municipal solid waste, with over half of this waste ultimately disposed of in landfills. Landfilling, as the most common waste management practice worldwide, is estimated to store 21%–42% of all plastics produced globally. Landfills represent dynamic environments where plastics undergo fragmentation and degradation via physical, chemical, and biological processes, leading to the formation of more complex pollutants known as microplastics (MPs). MPs are categorized as follows: “primary MPs,” deliberately produced small plastic particles, and “secondary MPs,” which are formed as a result of breaking down of larger plastic materials. Consequently, landfills act not only as sinks for plastic waste but also as significant sources and continuous emitters of MP pollution. MPs, composed of different polymers such as polypropylene (PP), polyethylene (PE), polystyrene (PS), polyethylene terephthalate (PET), and polyvinyl chloride (PVC), are present in landfills and in their leachate. MPs are persistent, nonbiodegradable pollutants and often act as the carriers of other contaminants. Due to the uneven surface and coarse texture, MPs strongly adsorb and transport a range of other hazardous micropollutants, including heavy metals, antibiotics, endocrine-disrupting chemicals, and persistent organic pollutants. Such interactions considerably increase the ecological threat of landfill leachates to terrestrial and aquatic ecosystems. In this review, we consolidate current scientific evidence on the sources, origin, formation, polymeric compositions, and environmental behaviors of MPs in landfill environments and also highlight the influence of landfill age on MP abundance, diversity, and physicochemical properties. Additionally, in the review, we examine the emerging ecological and human health risks associated with landfill-derived MPs, including their role as vectors of toxic chemicals and pathogens. Despite increasing awareness of MP contamination, literature specifically addressing landfills as active origins of MPs remains scarce. By synthesizing available knowledge, in this study, we underscore that landfills function as both reservoirs and significant emission sources of MPs, contributing to broader challenges of global plastic pollution. The findings highlight the critical need for systematic monitoring, advanced leachate treatment technologies, and integration of circular economy principles to mitigate risks associated with landfill-derived MPs and to ensure sustainable waste management strategies.